(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Today, myocardial infarction and its treatment are considered one of the most complex problems.In order to solve these problems, scientists from abroad and our republic are doing a lot of work.Also, it has been confirmed that cardiovascular death, total death and repeated myocardial infarction can be significantly reduced if prevention and cardiorehabilitation methods are used in time and on a large scale. The planning of such programs has been identified as a priority direction in the world, including in Uzbekistan.